A divergent spirochete strain isolated from a resident of the southeastern United States was identified by multilocus sequence typing as Borrelia bissettii. Issue 1 (December 2016) - Golovchenko, Maryna; Vancová, Marie; Clark, Kerry; Oliver, James; Grubhoffer, Libor; Rudenko, Nataliia
Abstract Background Out of 20 spirochete species fromBorrelia burgdorferi sensu lato (s.l.) complex recognized to date some are considered to have a limited distribution, while others are worldwide dispersed. Among those areBorrelia burgdorferi sensu stricto (s.s.) andBorrelia bissettii which are distributed both in North America and in Europe. WhileB. burgdorferi s.s. is recognized as a cause of Lyme borreliosis worldwide, involvement ofB. bissettii in human Lyme disease was not so definite yet. Findings Multilocus sequence typing of spirochete isolates originating from residents of Georgia and Florida, USA, revealed the presence of twoBorrelia burgdorferi sensu stricto strains highly similar to those from endemic Lyme borreliosis regions of the northeastern United States, and an unusual strain that differed from any previously described in Europe or North America. Based on phylogenetic analysis of eight chromosomally located housekeeping genes divergent strain clustered betweenBorrelia bissettii andBorrelia carolinensis, two species from theB.burgdorferi s.l. complex, widely distributed among the multiple hosts and vector ticks in the southeastern United States. The genetic distance analysis showed a close relationship of the diverged strain toB. bissettii . Conclusions Here, we present the analysis of the first North American human originated live spirochete strain that revealed close relatedness toB. bissettii . The potential ofB. bissettii to cause human disease, even if it is infrequent, is of importance for clinicians due to the extensive range of its geographic distribution.